ANALISIS STABILITAS BLOK ANGKUR/BACKSTAY JEMBATAN GANTUNG JURANGSARI KABUPATEN SEMARANG - Ahmad Munif; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
The suspension bridge construction program is part of President Joko Widodo's Nawa Cita Program, namely developing Indonesia from the outskirts. The location of this research is the Jurangsari Suspension Bridge Construction Project, Semarang Regency, while the object of this research is the stability of the anchor blocks.In this research, calculations were carried out on the stability of the anchor blocks. The data used includes design drawing data and soil investigation data at the location. The data was processed and analyzed using the Excel spreadsheet program.The results of the analysis concluded that the stability of the anchor block at the service limit conditions was safe against shear with SF=5.5 > 1.5 and overturning SF= 57.0 >1.5 while under extreme conditions/seismic it was safe against shear with SF= 6.81 >1.1 and overturning SF = 21.09 >1.1. The bearing capacity of the soil to withstand its own weight and the forces acting on the anchor block in the conditions of safe service limits on the allowable bearing capacity with maximum s= 132.52 kN/m2 and s minimum = 119.26 kN/m2, s maximum <s permit 292.137 kN/m2 or 2.20 times greater than the s maximum that occurs, whereas in extreme conditions the soil tension that occurs at s maximum = 190.09 kN/m2 and s minimum = 142.74 kN/m2, s maximum <s permit 292.137 kN/ m2 or 1.54 greater than the maximum s that occurs. Settlement that occurs in the anchor block under safe service limit conditions is Si = 0.441 cm and in extreme conditions is Si = 0.633 cm, both conditions the safety factor for the decrease is £ 1.0 cm.